Exercise metabolomics in pulmonary arterial hypertension: Where pulmonary vascular metabolism meets exercise physiology - Lee, Michael H.; Menezes, Thaís C. F.; Reisz, Julie A.; Ferreira, Eloara V. M.; Graham, Brian B.; Oliveira, Rudolf K. F. (Frontiers in Physiology, 2022)
Pulmonary arterial hypertension is an incurable disease marked by dysregulated metabolism, both at the cellular level in the pulmonary vasculature, and at the whole-body level characterized by impaired exercise oxygen consumption. Though both altered pulmonary vascular metabolism and abnormal exercise physiology are key markers of disease severity and pulmonary arterial remodeling, their precise interactions are relatively unknown. Herein we review normal pulmonary vascular physiology and the current understanding of pulmonary vascular cell metabolism and cardiopulmonary response to exercise in PAH. We additionally introduce a newly developed international collaborative effort aimed at quantifying exercise-induced changes in pulmonary vascular metabolism, which will inform about underlying pathophysiology and clinical management. We support our investigative approach by presenting preliminary data and discuss potential future applications of our research platform.